My Louisiana sky - Holt, Kimberly Willis (Square Fish, 2011)
Growing up in Saitter, Louisiana, in the 1950s, twelve-year-old Tiger Ann struggles with her feelings about her stern, but loving grandmother, her mentally slow parents, and her good friend and neighbor, Jesse.